2005
DOI: 10.1074/jbc.m501112200
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol Kinase α Regulates the Secretion of Lethal Exosomes Bearing Fas Ligand during Activation-induced Cell Death of T Lymphocytes

Abstract: Fas ligand (FasL) mediates both apoptotic and inflammatory responses in the immune system. FasL function critically depends on the different forms of FasL; soluble Fas ligand lacking the transmembrane and cytoplasmic domains is a poor mediator of apoptosis, whereas fulllength, membrane-associated FasL (mFasL) is pro-apoptotic. mFasL can be released from T lymphocytes, via the secretion of mFasL-bearing exosomes. mFasL in exosomes retains its activity in triggering Fas-dependent apoptosis, providing an alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(171 citation statements)
references
References 48 publications
5
166
0
Order By: Relevance
“…It has been demonstrated that FasL-mediated apoptosis can also be owing to the secretion of FasL-bearing exosomes/ microvesicles. 22 To exclude the detection of FasL released in exosomes into the culture medium, cell supernatants were subjected to ultracentrifugation before analyses. Although inhibitors of aspartyl and serine proteases (pepstatin A and AEBSF, respectively) did not show an obvious effect on FasL shedding, the wide-spectrum MP inhibitors GM6001 and TNF-a protease inhibitor (TAPI) led to a strong reduction of sFasL (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that FasL-mediated apoptosis can also be owing to the secretion of FasL-bearing exosomes/ microvesicles. 22 To exclude the detection of FasL released in exosomes into the culture medium, cell supernatants were subjected to ultracentrifugation before analyses. Although inhibitors of aspartyl and serine proteases (pepstatin A and AEBSF, respectively) did not show an obvious effect on FasL shedding, the wide-spectrum MP inhibitors GM6001 and TNF-a protease inhibitor (TAPI) led to a strong reduction of sFasL (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…22 To exclude the detection of FasL released in exosomes into the culture medium, cell supernatants were subjected to ultracentrifugation before immunoblot or ELISA analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The lipid mediator phosphatidic acid originating either from the activity of the diacylglycerol kinase [45] or from phospholipase D (PLD2) activities promotes exosome secretion [46].…”
Section: Regulated Secretionmentioning
confidence: 99%
“…Therefore understanding in depth the biogenesis and release mechanisms of exosomes in cells is essential. It has been shown that some lipid mediators could enhance their production [45,101]. On the reverse, decreasing the amount of tumor exosomes released by modifying the pH of MVB with amiloride enhances the efficacy of chemotherapeutic agents [102].…”
Section: E Pharmacology Of Exosomes: the Future Challengementioning
confidence: 99%
“…[10][11][12][13][14][15] The discovery of exosome involvement in these responses increased interest in the regulation of exosome biogenesis and secretory traffic, with special attention to the contribution of lipids such as ceramide and DAG, as well as DAG-binding proteins. 14,[16][17][18][19][20][21] These studies suggest that positive and negative DAG regulators may control secretory traffic. By transforming DAG into phosphatidic acid (PA), diacylglycerol kinase α (DGKα) is essential for the negative control of DAG function in T lymphocytes.…”
mentioning
confidence: 99%